NILAI-NILAI PENDIDIKAN DALAM NOVEL JATISABA KARYA RAMAYDA AKMAL - Suprihatma Suprihatma; Maulida Putri Rahmawati (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This paper aims to describe the educational values which is contained in Jatisaba novel by Ramayda Akmal and also describe alternative learning material for educational values in Jatisaba novel by Ramayda Akmal. The expected benefits are knowledge about the value of education in the novel Jatisaba by Ramayda Akmal, increasing appreciation of literary works for students, to provide information to readers about the value of education in the novel Jatisaba by Ramayda Akmal, and alternative junior high school learning materials. The research method used by researchers to analyze library methods and analysis methods with a dedactic approach. The research results show that the novel Jatisaba by Ramayda Akmal contains extrinsic elements of literary works, namely the value of education which consists of the value of religious education, the value of sociality education, the value of justice education, and the value of honesty education. Keywords: the value of education, literature, junior high school learning